2017
DOI: 10.1016/j.str.2017.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Cryoelectron Microscopy Reconstructions of the Pseudomonas aeruginosa and Neisseria gonorrhoeae Type IV Pili at Sub-nanometer Resolution

Abstract: We report here cryoelectron microscopy reconstructions of type IV pili (T4P) from two important human pathogens, Pseudomonas aeruginosa and Neisseria gonorrhoeae, at ∼ 8 and 5 Å resolution, respectively. The two structures reveal distinct arrangements of the pilin globular domains on the pilus surfaces, which impart different helical parameters, but similar packing of the conserved N-terminal α helices, α1, in the filament core. In contrast to the continuous α helix seen in the X-ray crystal structures of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
126
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(142 citation statements)
references
References 70 publications
16
126
0
Order By: Relevance
“…Each subunit is related to an adjacent subunit by, on average, a ~11.2 Å axial rise and ~96.0° azimuthal rotation, forming a 1‐start right‐handed helix, although these parameters are quite variable in PpdD. This symmetry is very typical for Type IV pili, such as those from P. aeruginosa (Wang et al , ), N. gonorrhoeae (Wang et al , ) and N. meningitidis (Kolappan et al , ) (Table ). The symmetry of PpdD pili differs from that of PulG pseudopili assembled by the same T2SS, which showed ~10.2 Å axial rise and 83.2° of twist (Lopez‐Castilla et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…Each subunit is related to an adjacent subunit by, on average, a ~11.2 Å axial rise and ~96.0° azimuthal rotation, forming a 1‐start right‐handed helix, although these parameters are quite variable in PpdD. This symmetry is very typical for Type IV pili, such as those from P. aeruginosa (Wang et al , ), N. gonorrhoeae (Wang et al , ) and N. meningitidis (Kolappan et al , ) (Table ). The symmetry of PpdD pili differs from that of PulG pseudopili assembled by the same T2SS, which showed ~10.2 Å axial rise and 83.2° of twist (Lopez‐Castilla et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…). Recent cryo‐EM reconstructions of several Tfp revealed that the filaments are right‐handed helical polymers of pilins held together by extensive hydrophobic interactions between their α1 helices, which run approximately parallel to each other within the filament core (Kolappan et al , ; Wang et al , ). Extensive sequence conservation in α1N (Fig.…”
Section: Tfp Assembly: Lessons From Monoderm Bacteriamentioning
confidence: 99%
“…Pilins and archaellins share a characteristic 'lollipop' shape consisting of a hydrophobic N-terminal kinked α-helix followed by a C-terminal β-strand rich globular domain (Figure 2) (Braun et al, 2016;Kolappan et al, 2016;Poweleit et al, 2016;Daum et al, 2017;Wang et al, 2017). Differences in the sizes of individual monomers lead to variations in the filament packing and diameters of the assembled filaments (Braun et al, 2016;Kolappan et al, 2016;Poweleit et al, 2016;Daum et al, 2017;Wang et al, 2017).…”
Section: The Filaments and Their Protomersmentioning
confidence: 99%
“…Differences in the sizes of individual monomers lead to variations in the filament packing and diameters of the assembled filaments (Braun et al, 2016;Kolappan et al, 2016;Poweleit et al, 2016;Daum et al, 2017;Wang et al, 2017). The central core of the filament is formed from bundles of the N-terminal α-helices of individual monomers (Figure 2).…”
Section: The Filaments and Their Protomersmentioning
confidence: 99%